Answer:
C. 125
Step-by-step explanation:
Given:
y₀ = h m
v₀ = 0 m/s
a = -10 m/s²
@ t − 1, y = 9/25 h m
@ t, y = 0 m
Find: h
Use constant acceleration equation:
y = y₀ + v₀ t + ½ at²
@ t:
0 = h + (0) (t) + ½ (-10) t²
0 = h − 5 t²
h = 5 t²
@ t − 1:
9/25 h = h + (0) (t − 1) + ½ (-10) (t − 1)²
9/25 h = h − 5 (t − 1)²
9/25 h = h − 5 (t² − 2t + 1)
9/25 h = h − 5 t² + 10 t − 5
0 = 16/25 h − 5 t² + 10 t − 5
Substitute:
0 = 16/25 (5 t²) − 5 t² + 10 t − 5
0 = 16/25 t² − t² + 2 t − 1
0 = -9/25 t² + 2 t − 1
0 = 9 t² − 50 t + 25
0 = (t − 5) (9t − 5)
t = 5/9 or 5
Since t > 1, t = 5.
Solving for h:
h = 5 t²
h = 125